2009
DOI: 10.2165/11313740-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Head Lice Treatments and School Policies in the US in an Era of Emerging Resistance

Abstract: Our study suggests that permethrin 1% was the most cost-effective treatment for those with a willingness to pay of <$US162 per cure. Sensitivity of lice to permethrin and the specific school head lice policy had major effects on the model. Thus, informing communities in a given geographical area about the degree of head lice resistance and sensitivity is necessary in order for the public to make a rational decision regarding treatment. Schools' head lice policies have a major effect on the cost of head lice tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…The 23.48 % infestation rate found in this study shows the problem of head lice among schoolchildren especially in schoolgirls aged [5][6][7][8][9][10][11][12] years. The previous studies in Thailand by Thavara et al [15] , Thanyavanich et al [16] and Fan et al [17] have reported the high infestation rate among primary schoolchildren in both urban and rural areas varied from 36.6 % to 88.4 % .…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The 23.48 % infestation rate found in this study shows the problem of head lice among schoolchildren especially in schoolgirls aged [5][6][7][8][9][10][11][12] years. The previous studies in Thailand by Thavara et al [15] , Thanyavanich et al [16] and Fan et al [17] have reported the high infestation rate among primary schoolchildren in both urban and rural areas varied from 36.6 % to 88.4 % .…”
Section: Discussionmentioning
confidence: 86%
“…In our study was conducted among the [5][6][7][8][9][10][11][12] years old in 12 primary schools from Ladkrabang District, eastern area of Bangkok, Thailand. The 23.48 % infestation rate found in this study shows the problem of head lice among schoolchildren especially in schoolgirls aged [5][6][7][8][9][10][11][12] years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations